The Rationality Conundrum: Exploring Herd Mentality among Individual Investors in the Indian Stock Market - G., Suresh; Loang, Ooi Kok (Indian Journal of Finance, 2024)
Purpose : The present study aimed to explore the factors contributing to and interaction of rationality and irrationality in the herding behavior of investors in the Indian stock markets. Methodology : A structured questionnaire was developed to explore the driving factors of rational and irrational herding based on the literature to explore the interplay between rational and irrational herding. The required data for the study was collected from 384 respondent investors selected through snowball sampling. Further, the study adopted a casual research design to examine the hypotheses framed through the literature. Findings : The study found that many rational and irrational factors are causing Indian retail investors’ herding behavior. Self-attribution, noise trading, and social influence are the causes of rational herding; whereas, spurious herding and the illusion of control are drivers of irrational herding behavior. Research Implications : Policymakers and stock market regulators, among other stakeholders, should take note of the study’s conclusions. Additionally, this research aids in the formulation of a plan to reduce investors’ herding behavior. Originality : The majority of the research on herding behavior in stock markets focused on the variables that lead to herding; there are not many studies on how rational and irrational elements interact to cause herding behavior. This study contributes to the body of knowledge on herding behavior in the stock market.